ESTIMATED ELECTRICITY BILLING SYSTEM AND ITS EFFECTS ON CONSUMERS IN RESIDENTIAL AND BUSINESS CENTRES IN WUKARI METROPOLIS, TARABA STATE - Abubakar Ahmadu; Vyonkhen Tanko Nacho (International Studies Journal)
Estimated billing system has been adopted ever since the manual metering system became moribund in Nigeria. It is a corporate crime that has been paltry explored in the corpus of Criminology. Extant findings on estimated billing have exonerated utility companies while classifying consumers of electricity as perpetrators of power theft. This study set out to investigate the effects of estimated billing on consumers in residential houses/business centres in Wukari town, and explore the causes and/or factors leveraging the adoption of the payment platform for energy charges as well as offer feasible ways of addressing the problem. The study adopted survey design with its accompanying instruments like questionnaire and indepth interview. A sample size 131 was determined using the Cochran’s formula for smaller population. Only 128 copies of the questionnaires were retrieved and found useable at 97.8% return rate. Ten (10) persons made up the panel of indepth interview. Descriptive and inferential statistics like percentages and linear regression were used respectively to address the research questions and test the hypothesis. Findings reveal that estimated billing has affected consumers by charging them above their actual energy consumption. This is in addition to triggering physical confrontation between consumers and marketers of power companies as well as discouraged consumers from making full payment of estimated charges for a month under review. However, the quest to generate revenue accounted for the adoption estimated billing by Power Company among other factors like duration of power supply and the unwillingness of consumers to acquire prepaid meters. It is recommended among others the adoption of Artificial Neural Network (ANN) to gauge consumers’ energy consumption pending the provision of prepaid meters and that National Electricity Regulatory Commission (NERC) should intensify efforts in the provision of free and/or subsidized prepaid meters to consumers.